Aktivitas Komunikasi Pemasaran Terpadu (IMC) Pemerintah Kota Ambon dalam Mengkomunikasikan Brand Ambon City Of Music Melalui Kegiatan Tiga Pilar IMC - Solsolay, Arthur (Universitas Semarang, 2016)
Ambon city is one of the tourist destinations in the province of Maluku, kept the charm and appeal of natural, historical, religious, culinary, education, art, culture and customs. To develop and trigger the development of musical art in the city of Ambon, Ambon city government felt the need to form a brand that became a brand differentiator and became icons of tourism in Ambon. Brand